Floristic characteristics of riparian pan vegetation from the Ndumo Game Reserve, South Africa - M. Whittington; M.D. Panagos; G. Malan (Journal of Animal and Plant Sciences, 2016)
The aim of this study was to identify habitat types according to plant communities that surround the Banzi, Shokwe and Nyamithi pans located in the Ndumo Game Reserve. This hydrophytic vegetation thrives on stream and riverbanks, and thus plays a direct role in the functioning of both river systems and the flanking terrestrial landscape. Banzi, Shokwe and Nyamithi pans were classified into two different wetland systems. Banzi and Shokwe pan as a Riverine system and Nyamithi Pan as a Lacustrine system. Around the pans, 14 sampling sites were positioned and 34 quadrats or belts were sampled within these sites. Eighty-six plant species were identified around the three pans, where the dominant growth form was mostly trees. The four floristic units obtained via a classifications process were conformed into three habitat types, the Mudflat, Beach and Reedbed (MBR) Habitat Type, Riparian Forest Habitat Type and the Fringe Terrestrial Habitat Type. Due to their uniqueness, the pans add value to the Reserve and thus need to be conserved and monitored. This study provided a baseline data set by which future changes in the specific floristic characteristics (species composition, structure, cover and density) of the riparian vegetation surrounding the pans can be monitored.
Keywords: Ndumo Game Reserve; pan; riverine; lacustrine; floristics; riparian; wetland